Effect of the calisthenics exercises on static and dynamic balance in tennis players - Genç, H. (International Journal of Applied Exercise Physiology, 2020)
The purpose of the study is to examine the effects of calisthenics exercises performed with tennis trainings on static and dynamic balance performances. 17 male tennis players with ages of 20.82 + 4.42 years, height 1.80 + 0.03 m, body weight 58.75 kg participated in the study voluntarily. The tennis players participating in the study were randomly divided into 2 groups. 9 tennis players in the experimental group (EG) performed calisthenics exercise and tennis training, and 8 tennis players in the control group (CG) performed only tennis training. The study lasted a total of 8 weeks, with 3 workouts per week. Study; height length, body weight, BMI, static balance and dynamic balance measurements were taken. Static balance measurements were measured with ALFA Stabilometric Platform device and dynamic balance Y test. Statistical analysis findings of the subjects were evaluated in the SPSS 22 program. As a result of the study, statistically improvement was observed in eyes with open-to-back standard deviation (34.47%), right-left standard deviation (20.82%) and static balance (28.29%) in calisthenics exercise. In DG, positive developments were observed in eyes with open-to-back swing speed (23.23%), left-to-left swing speed (31.68%) and total swing speed (27.16%), (p <0.05), There was no significant difference in CG (p> 0.05). It has been determined that EG, which performs calisthenics exercise in the eyes closed static balance score, has a 25.17% improvement. Significant improvements were observed in EG with eyes closed forward-to-back oscillation speed by 20.40%, right-to-left oscillation rate by 26.23%, and total oscillation speed by 22.98% (p <0.05). According to the results of Y balance test, it was determined that EG performing calisthenics exercise showed significant improvement in Anterior value of 3.47%, Posteromedial value of 3.31% and Posterolateral value of 3.65% (p <0.05). It was determined that EG showed an improvement of 4.27% in Anterior value for nondominant foot, 3.24% for Posteromedial value and 3.41% for Posterolateral value (p <0.05). When the results are analyzed, both static balance scores and oscillation speeds and dynamic balance results are seen in the findings of the study, where more improvement was detected in EG, which performs calisthenics exercise, compared to CG.